2020
DOI: 10.1016/bs.irn.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of stress-relieving strategies in regulating patterns of cortisol secretion and promoting brain health

Abstract: Stress-relieving strategies and brain health Full title:Effectiveness of stress relieving strategies in regulating patterns of cortisol secretion and promoting brain health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 95 publications
2
14
0
Order By: Relevance
“…To adapt to the social, emotional triggers, and physical encounters of life, students can establish holistic self-stress management strategies for growth to achieve overall well-being while in school; therefore, reap the lifetime benefits. Given that "stress refers to that quality of experience, produced through a person-environment transaction, that, through either hyperarousal or under arousal, results in psychological or physiological distress [103]", MBPA, such as yoga, has revealed encouraging efficacy [5,104]. Cortisol, as a primary stress hormone produced by the sympathetic nervous system (SNS) and the hypothalamicpituitary-adrenocortical (HPA) axis, aids in controlling blood pressure along with many other neurological and physiological regulatory effects [105].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To adapt to the social, emotional triggers, and physical encounters of life, students can establish holistic self-stress management strategies for growth to achieve overall well-being while in school; therefore, reap the lifetime benefits. Given that "stress refers to that quality of experience, produced through a person-environment transaction, that, through either hyperarousal or under arousal, results in psychological or physiological distress [103]", MBPA, such as yoga, has revealed encouraging efficacy [5,104]. Cortisol, as a primary stress hormone produced by the sympathetic nervous system (SNS) and the hypothalamicpituitary-adrenocortical (HPA) axis, aids in controlling blood pressure along with many other neurological and physiological regulatory effects [105].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol, as a primary stress hormone produced by the sympathetic nervous system (SNS) and the hypothalamicpituitary-adrenocortical (HPA) axis, aids in controlling blood pressure along with many other neurological and physiological regulatory effects [105]. Therefore, engaging in stress alleviating practices promotes a healthy 24 h cortisol pattern, regulation, secretion, and physical activity is a paramount lifestyle behavior regardless of age and the duration [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies show that serum concentrations of both salivary IgA, a marker of immune function, and oxytocin, a hormone involved in human connection, increase after singing lessons [14,15]. Several studies also report decreases in cortisol, a hormone integral to the stress response, for subjects during the act of singing and other creative activities [13,14,[16][17][18][19][20]. Group singing in particular has also been shown to reduce stress and arousal, measured by serum levels of ACTH, a precursor to cortisol [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this article evidences related to yoga and its role in PD will be reviewed in a detailed fashion. https://doi.org/10.29328/journal.jnnd.1001033 patterns of cortisol secretion which in turn can promote brain health and delay progression of symptoms and halt the disease process of many clinical disorders and neurodegenerative diseases including PD [7,8]. A recent meta-analysis further showed that mind-body exercises like yoga and tai chi can provide signi icant improvements in motor function, depressive symptoms, and quality of life in patients with PD [9], in line with the study of Kwok, et al, which also found that these exercises demonstrated immediate moderate to large bene icial effects on motor symptoms, postural instability, and functional mobility among individuals with mild to moderate PD [24].…”
Section: Introductionmentioning
confidence: 99%